Gene Expression Profiling of Glioblastoma to Recognize Potential Biomarker Candidates - Li, Qiang; Aishwarya, S.; Li, Ji-Ping; Pan, Dong-Xiao; Shi, Jia-Pei (Frontiers in Genetics, 2022)
Glioblastoma is an aggressive malignant tumor of the brain and spinal cord. Due to the blood-brain barrier, the accessibility of its treatments still remain highly challenging. Unfortunately, the recurrence rates of Glioblastoma upon surgery is very high too. Hence, understanding the molecular drivers of disease progression is highly valuable. In this study, we aimed to investigate the molecular drivers responsible for the Glioblastoma progression and identify valid biomarkers. Three microarray expression profiles GSE90604, GSE50601 and GSE134470 containing healthy and Glioblastoma affected samples revealed overlapping differentially expressed genes (DEGs) of which 23 are upregulated and 38 downregulated with thresholds of log2FC > 1 and p-value < 0.05. The interrelational pathway enrichment analysis elucidated the halt of cell cycle checkpoints, activation of signaling pathways and arrived at 6 predominant hub genes. Validation of hub genes in comparison with the Cancer Genome Atlas Datasets identified the potential biomarkers of Glioblastoma. The study evaluated two significantly upregulated genes, SPARC (Secreted Protein Acidic And Cysteine Rich) and VIM (vimentin) for glioblastoma. The genes, CACNA1E (Calcium Voltage-Gated Channel Subunit Alpha1 E), SH3GL2 (SH3 Domain Containing GRB2 Like 2, Endophilin A1), DDN (dendrin) were identified as under-expressed genes in glioblastoma compared to the normal and pan-cancer tissues along with prominent putative prognostic biomarker potentials. The genes DDN, SH3GL2 and CACNA1E were classified based on the subtypes and found to be upregulated in proneural and mesenchymal subtypes of glioblastoma respectively. The mutational analysis also revealed the benign, possibly and probably damaging substitution mutations. The correlation between the DEG expression and survival in glioblastoma was evaluated using the Kaplan- Meier plots and VIM had a greater life expectancy of 60.25 months. Overall, this study identified key candidate genes that might serve as predictive biomarkers for glioblastoma.